Postnatal care after gestational diabetes – a systematic review of clinical practice guidelines - Phyllis Ohene-Agyei; Ariba Iqbal; Jane E. Harding; Caroline A. Crowther; Luling Lin (BMC Pregnancy and Childbirth)
Abstract Background Gestational diabetes mellitus (GDM) is the most common metabolic disorder in pregnancy and later is associated with an increased risk of type 2 diabetes and other metabolic disorders. Consistent and evidence based postnatal care is key to improving maternal long-term health. We therefore aimed to review and compare recommendations of national and international clinical practice guidelines (CPG) for postnatal care after GDM and identify any evidence gaps in recommendations needing further research. Methods We searched five databases and forty professional organization websites for CPGs providing recommendations for postnatal care after GDM. CPGs which had full versions in English, endorsed, prepared, or authorized by a professional body, and published between 2013 and 2023 were eligible for inclusion. Two reviewers independently screened the articles, extracted the recommendations, and appraised the included CPGs using the Appraisal of Guidelines, Research, and Evaluation (AGREE) II tool. Results Twenty-six CPGs from 22 countries were included. Twelve CPGs (46%) were appraised as low quality with the lowest scoring domains being rigor of development and editorial independence. We found little high certainty evidence for most recommendations and few recommendations were made for maternal mental health and postpartum metabolic screening. Evidence gaps pertained to postpartum glucose screening, including frequency, tests, and ways to improve uptake, evaluation of effective uptake of lifestyle interventions, and ongoing long-term follow up care. Conclusions Most of the postnatal care recommendations in GDM guidelines are not based on high certainty evidence. Further efforts are needed to improve the global evidence base for postnatal care after GDM to improve long-term maternal health. Protocol Registration This review was registered in PROSEPRO (CRD42023454900).